Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1530/rep-10-0378
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a high-fat, high-cholesterol diet on markers of uterine contractility during parturition in the rat

Abstract: Increasing levels of obesity within women of reproductive age is a major concern in the UK. Approximately, 13% of women aged !30 and 22% of 31-to 40-year-old women are obese. Obesity increases complications during pregnancy and the risk of caesarean section due to prolonged labour and poor uterine activity. The aim was to investigate whether a high-fat, high-cholesterol (HFHC) diet decreases markers of uterine contractility during parturition in the rat. Female Wistar rats were fed control (CON, nZ10) or HFHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…Decreased Cx43 expression is observed in multiple tissues upon lipid overload, including in adipose tissues after a HFD challenge (Elmes et al, 2011; Keller et al, 2008; Noyan-Ashraf et al, 2013). Cx43 expression has an inverse correlation with glucose and insulin levels, and is implicated in aging and obesity in two mouse strains (Keller et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased Cx43 expression is observed in multiple tissues upon lipid overload, including in adipose tissues after a HFD challenge (Elmes et al, 2011; Keller et al, 2008; Noyan-Ashraf et al, 2013). Cx43 expression has an inverse correlation with glucose and insulin levels, and is implicated in aging and obesity in two mouse strains (Keller et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Connexins are gap junction trans-membrane proteins that assemble to form a gap junction; Con43 is the predominant connexin involved in the initiation of MSMC contractions at term (Chow and Lye, 1994). A study in pregnant rats on a high Ch diet showed that high Ch is associated with a decrease in Con43 protein in the myometrium, suggesting possible implications for uterine contractility (Elmes et al , 2011). A study in isolated rat cardiac myocytes demonstrated that gap junctional intracellular communication (GJIC) disturbance, by either silencing the gene for Con43 or by addition of specific drugs, such as heptanol, induced a significant reduction in Ca 2+ transients, suggesting that Con43 may be involved in the regulation of basal Ca 2+ signalling in these cells (Li et al , 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A high fat diet induced low CX43 protein levels, which was restorable by pharmacological intervention in cardiac tissues of 32 wk old mice (Noyan-Ashraf et al , 2013). Also, decreased CX43 levels in autopsied uterine tissue were demonstrated in rats fed a high fat and high cholesterol diet (Elmes et al , 2011). Our data thus exhibit that CX43 protein levels are decreased during progressive obesity consistent with data in non-ovarian tissues.…”
Section: Discussionmentioning
confidence: 99%